Effect of Fiscal Policy on Economic Growth Sustainability in Egypt - Hamdy, Olfat (International Journal of Economics and Financial Issues, 2025)
This study analyses how fiscal policy influences economic growth in Egypt by analyzing its components and building a model that captures both the short- and long-run economic patterns. The paper uses a time series methodology to investigate the relation between various fiscal policy measures and growth from 2000 to 2022. While tax receipts were separated into distortionary and non-distortionary categories, government spending was categorized as productive or unproductive. Our results show that while income tax has no discernible effect on GDP, non-tax revenue and wages significantly impact economic growth at the 5% level. Additionally, government expenditures and investments in education and health were viewed as insignificant for immediate growth. These observations are crucial for Egyptian policymakers since they highlight the necessity to increase public expenditures while reducing wasteful spending.